2017
DOI: 10.1016/j.pathol.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors in breast cancer invasion: a mathematical modelling review

Abstract: This review presents a brief overview of breast cancer, focussing on its heterogeneity and the role of mathematical modelling and simulation in teasing apart the underlying biophysical processes. Following a brief overview of the main known pathophysiological features of ductal carcinoma, attention is paid to differential equation-based models (both deterministic and stochastic), agent-based modelling, multi-scale modelling, lattice-based models and image-driven modelling. A number of vignettes are presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 94 publications
0
23
0
Order By: Relevance
“…In addition to this, results of using multiscale modelling of growing tumors had long term negative effects on phenotypes [27]. Conclusions about negative effects of experimentally verified models of breast cancer on phenotypes can be found in the paper [28]. Experiences and mistakes that have been approved and verified through the given works, limit the research in this paper in the conclusions.…”
Section: Results Anddiscussionmentioning
confidence: 92%
“…In addition to this, results of using multiscale modelling of growing tumors had long term negative effects on phenotypes [27]. Conclusions about negative effects of experimentally verified models of breast cancer on phenotypes can be found in the paper [28]. Experiences and mistakes that have been approved and verified through the given works, limit the research in this paper in the conclusions.…”
Section: Results Anddiscussionmentioning
confidence: 92%
“…257 This was corroborated by another multiscale study, which found that environmental pressure encouraged predictable phenotypes, first with models and then experimentally verified with breast cancer models. Readers interested in more comprehensive knowledge of this type of modeling might refer to a recent review by Simmons et al 258 The extant examples of computational modeling only scratch the surface a field that is becoming increasingly accessible, and QMIB will be essential to validating such promising multiscale models in the future.…”
Section: Computational Cancer Modelingmentioning
confidence: 99%
“…Breast cancer, the most common female cancer, is highly heterogeneous and is probably caused by numerous changes in the genome of specific cells over extended time periods . Changes of normal‐phenotype breast cells to cancerous‐phenotype cells are affected by a series of factors, such as the local and non‐native environment, lifestyle, dietary habits, and genetic inheritance, which can disrupt cells' physical characteristics, behavior, and communication pathways .…”
Section: Introductionmentioning
confidence: 99%
“…Changes of normal‐phenotype breast cells to cancerous‐phenotype cells are affected by a series of factors, such as the local and non‐native environment, lifestyle, dietary habits, and genetic inheritance, which can disrupt cells' physical characteristics, behavior, and communication pathways . Ductal carcinoma in situ (DCIS) of the breast, a noninvasive and nonobligate precursor lesion, represents a transition from normal tissue to an invasive ductal breast carcinoma (IDC) through a multifactorial process …”
Section: Introductionmentioning
confidence: 99%